How Should We Blend? The Impact of Blending Social Networks on High School Students' Achievement and Social Networking Behaviors - Cimen, Ali; Yilmaz, M. Betul (TURKISH EDUCATION ASSOC, 2017)
This study examines the effect of blended learning environment, where social networks are utilized to supplement or enrich classroom environment, on the academic achievement and social network usage behaviors of high school students. The study was carried out with a total of 104 students in 10th grade of a state high school in Istanbul. It involved one control and two experimental groups. The students in the first experimental group were obliged to use social networking which aimed at complementing the class environment. The social networking environment was presented to the students in the second experimental group with the purpose of enriching the class environment. Yet, participation to this networking was voluntary. For the control group, all activities were held in face-to-face classroom setting. A 24-item test was developed to measure students' academic achievement and administered as pre- and post-test. In addition, all activities of students on the social network were recorded to measure their social networking behaviors, and these records were used to calculate total activity scores, and course-related activity scores. Academic achievement test scores of both experimental groups were found to be significantly higher than those of the control group. Another finding of the study is that, in the social network, total course related activity scores did not significantly differ between experimental groups. Findings indicate that using social networks to supplement or enrich classroom setting increases student achievement. This increment is higher when the social network is used to supplement classroom setting instead of using social network as enriching medium. Suggestions were also provided.
Keywords: Social network; Blended learning; Technology integration into education; High school students; Academic achievement; COLLEGE-STUDENTS; FACEBOOK USE; Education & Educational Research